Deletion of the Loop Linking Two Domains of Exo-Inulinase InuAMN8 Diminished the Enzymatic Thermo-Halo-Alcohol Tolerance - Cen, Xiaolong; Zhang, Rui; He, Limei; Tang, Xianghua; Wu, Qian; Zhou, Junpei; Huang, Zunxi (Frontiers in Microbiology, 2022)
Inulin is the rich water-soluble storage polysaccharide after starch in nature, and utilization of inulin through hydrolysis of exo-inulinases has attracted much attention. Thermo-halo-alcohol tolerance is essential for exo-inulinase applications, while no report reveals the molecular basis involved in halo-alcohol tolerance of exo-inulinases via experimental data. In this study, two loops of exo-inulinase InuAMN8, including the loop built with 360GHVRLGPQP368 linking domains of Glyco_hydro_32N and Glyco_hydro_32C and another loop built with 169GGAG172 in the catalytic domain, were deleted to generate mutants MutG360Δ9 and MutG169Δ4, respectively. After heterologous expression, purification, and dialysis, InuAMN8, MutG169Δ4, and MutG360Δ9 showed half-lives of 144 min, 151 min, and 7 min at 50 °C, respectively. InuAMN8 and MutG169Δ4 were very stable while MutG360Δ9 showed a half-life of approximately 60 min in 5.0% (w/v) NaCl, and they showed half-lives of approximately 60 min in 25.0%, 25.0%, and 5.0% (w/v) ethanol, respectively. Structural analysis indicated that two cation-π bonds, which contributed to thermal properties of InuAMN8 at high temperatures, broke in MutG360Δ9. Four basic amino acid residues were exposed to the structural surface of MutG360Δ9 and formed positive and neutral electrostatic potential that caused detrimental effects on halo-alcohol tolerance. The study may provide a better understanding of the loop–function relationships that are involved in thermo-halo-alcohol adaptation of enzymes in extreme environment.